Headspace solid phase microextraction/gas chromatography–mass spectrometry combined to chemometric analysis for volatile organic compounds determination in canine hair: A new tool to detect dog contamination by visceral leishmaniasis - Oliveira, Lidia S. de (2008)
Acesso restrito: Texto completo. p. 392-398